“Something to Live for”: Experiences, Resources, and Personal Strengths in Late Adulthood - Russo-Netzer, Pninit; Littman-Ovadia, Hadassah (Frontiers in Psychology, 2019)
Due to increased life expectancy, the population segment of older adults has grown the fastest. The global phenomenon of population aging raises important questions regarding successful, positive, active, and meaningful aging. Given that aging is often characterized by declines in physical and mental health and increased risk for social isolation and depression, and given that the concept of well-being in old age is both elusive and complex, the present study explored how aging is experienced through a “bottom-up,” open-ended approach. Thirty-one in-depth semi-structured personal interviews were conducted with adults aged 60 and above in order to explore the question: what concerns older adults in their day-to-day living, and what are their perceived resources? The findings illuminated three prominent themes: (1) central concerns described by the participants as characterizing their experience at this life stage; (2) strategies employed by the participants to cope with concerns and to live a meaningful life in old age; and (3) resources and character strengths that facilitate coping strategies and enable thriving. Theoretical and practical implications of the findings are discussed.